Cassidy Reed: capstone - Reed, Cassidy, artist (Colorado State University. Libraries, 2021)
The artist's statement: My name is Cassidy Reed and I am a graphic designer. I find that art is a way that I can express myself in a way that writing down my thoughts would take place. It is a passion and a drive of mine to add color into the world. At a young age I would wonder around my grandparents photo lab admiring the art on the walls. It ranged from photography to paintings. The colors would change the way the wall looked and the subject would create a story. I soon realized that art is everywhere. From the design that you see on your school textbooks to the way the type is organized in a simple Coke a Cola logo and I fell in love. In my work I try to explore many different techniques physical and digital to achieve my desired outcome. I am always trying to learn new processes. I mostly focus in digital using adobe programs such as Illustrator and photoshop. I also have some knowledge in animation which I am continuing to learn more in. I always like to start with and idea and play around with it on paper until I feel really good about it. After that I will move into the digital or physical art of the piece working my way through each step. If it is a physical piece first then I will go in on photoshop and make the work more vibrant and brighter so that the original color come through more. Sometimes I will also combine it with other physical art to create a montage. Being able to make the world more colorful than I left it is my passion.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design